A diverse rotation of corn-soybean-winter wheat/double crop soybean with cereal rye after corn reduces tile nitrate loss - Gentry, Lowell E.; Mitchell, Corey A.; Green, John M.; Guacho, Carlos; Miller, Eric; Schaefer, Dan; Vasquez, Annette K.; Yu, Zhongjie (Frontiers in Environmental Science, 2025)
Artificial drainage via subterranean drainage pipes called tiles transport nitrate from fields to streams, impairing downstream surface waters. Increased crop rotational diversity may conserve nitrogen, support greater system resiliency, and reduce tile nitrate loss. This 9-year study compares tile nitrate loss under a 3-year rotation of corn-soybean-winter wheat/double crop soybean plus cereal rye after corn versus a conventionally managed 2-year corn-soybean rotation. Tile flow and tile nitrate concentration were measured from 2015 through 2023 to determine annual flow weighted mean concentrations and loads of tile nitrate. Cereal rye following corn greatly reduced annual tile nitrate; however, more than 6 Mg ha−1 of above ground biomass may have decreased soybean yield. Winter wheat was efficient at using split-applied fertilizer nitrogen (N) as annual tile nitrate concentrations were reduced similar to cereal rye. Double crop soybean after winter wheat may be the most productive phase of the rotation; however, an early killing freeze greatly reduced soybean yield and increased tile nitrate loss. Interestingly, the subsequent corn crop may have benefitted from this unexpected N source. Overall, tile nitrate loss was approximately 50% less in the diverse 3-year rotational system, suggesting that a more diverse rotational system is efficient at retaining N, conserving nitrogen in the field, and reducing N loss to surface water. This study demonstrated proof of concept that a more diverse crop rotation can reduce tile nitrate loss from fields to streams, while maintaining crop productivity.